Effectiveness of сavutilide in restoring sinus rhythm in patients with atrial fibrillation and flutter following prior unsuccessful electrical cardioversion - Kh. M. Dzaurova; N. Yu. Mironov; Yu. A. Yuricheva; M. M. Belyaeva; S. F. Sokolov; N. A. Mironova; S. P. Golitsyn; O. Yu. Korennova; I. M. Zueva; E. A. Turusheva; D. S. Terekhov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effectiveness and safety of cavutilide in patients with a history of unsuccessful cardioversion to terminate current persistent and paroxysmal atrial fibrillation (AF) episode.Material and methods. The retrospective study included 55 patients (mean age 60±8 years; male/female ratio 37/18) with paroxysmal (n=15) and persistent (n=40), who had unsuccessfully attempted to terminate the current episode of arrhythmia using electrocardiography. All patients received сavutilide in the intensive care unit according to the following regimen: 5 μg/kg-5 μg/kg-10 μg/kg-10 μg/kg. After each bolus and before the next one, ECG parameters (rhythm, QT interval) and the patients’ general condition were assessed; the interval between administrations was 15 minutes. Administration was halted if sinus rhythm (SR) was restored, heart rate (HR) fell below 50 bpm, QTc exceeded 500 ms, or arrhythmogenic effects occurred. Patients were monitored telemetrically for 24 hours to assess efficacy and safety.Results. SR was restored in 47 (85.4%) out of 55 patients, with a median restoration time of 40 [15-240] minutes. Five patients (9%) achieved SR after the initial of 5 μg/kg dose. Sixteen additional patients responded to 10 μg/kg (cumulative efficacy: 38%). Nine further patients achieved SR at 20 μg/kg (cumulative efficacy: 54.5%). The remaining patients required the maximum 30 μg/kg dose. QTc prolongation >500 ms occurred in 12 (21.8%) patients, though none developed sustained ventricular arrhythmias. Transient HR reduction <50 bpm occurred in 4/55 patients (7.2%) during arrhythmia termination.Conclusion. Cavutilide demonstrates high effectiveness and safety in restoring heart rhythm in patients with prior unsuccessful electrical cardioversion attempts. These findings support considering pharmacological cardioversion with cavutilide in such cases.